Clay Cracks Properties in Some Soils of Mesopotamia plane / Iraq - Raid SH. Jarallah; S. K. Essa (Al-Qadisiyah Journal For Agriculture Sciences, 2016)
In order to investigate clayey cracks and their properties. Seven soils sites (Afak Vertic-Torrifluvent , Al-Diwaniyah Typic-Torrifluvent , Al-Taleea Typic-Torrifluvent , Babel Vertic-Torrifluvent , Agriculture college Typic-Torrifluvent , Al-Wahda Vertic-Torrifluvent and Al-Raid project Typic-Torrifluvent) were chosen for this study. Some field morphological properties of cracking mass (numbers of cracking mass, crack's length , crack's width , crack's depth , thickness of hard part , thickness of friable part , surrounding of cracking mass and their shapes) were studied. Results of morphological discretion of cracking mass showed there were some different in shape , width and depth depending on the plasticity , specific and quantitative of clay minerals, depth of ground water , period of growth season and land use.